Ордер в європейській архітектурній теорії ХІХ – початку ХХІ століття - Павлова, А. В.; Pavlova, A. (Видавництво Львівської політехніки, 2017)
На основі аналізу літературнихд жерел у статті розглянуто особливості розвитку ордера в архітектурній теорії ХІХ – початку ХХІ століття. Проаналізовано сучасні праці, присвячені семантиці та метафорі ордерних систем, що стали актуальною проблемою ХХ століття, витіснивши пошуки пропорцій та спроби канонізації ордера попередніх періодів на задній план.

The article presents a review of the specific features of order development in architectural theory of the 19th – early 21st century as based on literary sources analyzed. It offers analysis of contemporary works on semantics and metaphor of order systems which became a relevant problem of the 20th century, making the search for proportions and the attempts to canonize order fade to the background. The order has always been an essential element of architectural composition as well as the main means of artistic expression of architecture of many historical periods. History of studies on the forms of order has spanned over two thousand and five hundred years. Yet, despite such a long time, not only does the interest in order remain as strong as ever but it also increases due to peculiarities of order compositions. During the 15th–18th centuries the main focus of order studies was given to its construction, actual physical form and parameters. Starting with the 20th century an increased number of works written was dedicated to research of the artistic image of order and its semantics. The 18th – 19th centuries became a major turning point in the development of architectural practice, theory and training. It is characterized by a fundamental change in architectural thought orientation; discovery of new objects of study and creation of new objects and content of artistic activity; development of new methods of research, design and training; and consequently, appearance of a new system of concepts and ideas. Architectural theorists of the 20th century sought to create a new style but the preconditions for creation of new architectural forms, which would be fundamentally and drastically different from the old order, did not exist. Principles of architectural theory were based primarily on the need to revive architecture in the sense of its artistic truth when expressing purpose, design and veracity of the materials used. The presence of these principles was gradually increasing in architectural development of the 19th century, both in theoretical statements of architects and in the buildings themselves. Theoretical views were divided: some of them, following Vitruvius, held to the opinion that order is a stone representation of a wooden construction, while others believed that the Greek order was created directly in stone. Ideas of some theorists who believed that architecture was supposed to be a match between structure and appearance laid the foundation for 20th century architecture. The second half of the 19th century also marked an interest in the Renaissance period. Many works on the history of architecture based on generalized material were published at the time. The 20th century witnessed a growth of interest in semantics in all areas of science and art, and order was no exception. Not only were architects interested in structure of order and its canons but they also faced a much more relevant and poorly researched problem at the time – semantics of architectural order. This brings up a question as to why the order has not lost its relevance and is still used after so many years, though not in its original classical form, remaining the basis for succeeding styles. In search for answer to this question, architectural theory has been recently updated with new research which changes professional understanding of the laws of creation and understanding of architecture.
Order in European architectural theory of the 19TH – early 21ST century
Keywords: ордер; теоретики архітектури; семантика; архітектурні праці; order; architectural theorists; semantics; architectural works; 72.03; 72.014